Studi Perilaku Penularan Penyakit HIV dan AIDS di Wangi-Wangi Kabupaten Wakatobi Tahun 2025 - Setiawan Marlino; Fikki Prasetya; Hartati Bahar (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Human Immunodeficiency Virus (HIV) is a virus that attacks the human immune system, so that humans infected with this virus cannot fight various types of diseases that attack their bodies. Meanwhile, Acquired Immune Deficiency Syndrome (AIDS) is a syndrome or collection of symptoms of a disease caused by the Human Immunodeficiency virus or better known as HIV. This research aims to determine the description of knowledge, attitudes, subjective norms and perceived behavioral control of PLWHIV regarding HIV and AIDS in Wangi-Wangi, Wakatobi Regency in 2025. This type of research is qualitative research using a phenomenological approach. Informants in this study were divided into two categories, namely, key informants were PLWHIV and ordinary informants were health workers. Data collection methods use in-depth interviews and observation. The results of this study show that PLWHIV knowledge regarding HIV and AIDS is still lacking because before they were diagnosed positive they did not find out about HIV and AIDS, the attitude of PLWHIV was still not good enough because before they were diagnosed positive they did not feel worried, they felt normal, some even felt happy in carrying out behavior at risk of contracting HIV and AIDS, the subjective norms of PLWHIV were influenced by friends, husbands and the people around them, which gave rise to a sense of confidence in PLWHIV to carry out risky behavior, the perception of behavioral control of PLWHIV is still not good enough because before being diagnosed positively, there is a feeling of curiosity and feeling of loneliness, which causes unstable self-control which is a trigger for carrying out risky behavior of contracting HIV and AIDS.